Outpatient parenteral antimicrobial therapy (OPAT) in the UK: findings from the BSAC National Outcomes Registry (2015–19). (21st February 2022) - Gilchrist, Mark; Barr, David; Drummond, Felicity; Muir, Alison; Williams, John; Scriven, James; Snape, Susan; Hemsley, Carolyn; Durojaiye, Chris O; Patel, Sanjay; Andrew Seaton, R.
Abstract: Background: Reporting of outpatient parenteral antimicrobial therapy (OPAT) outcomes with national benchmarking is key to informing service development and supporting quality improvement. Objectives: To analyse and report on data collected by the BSAC OPAT National Outcomes Registry from 2015 to 2019. Methods: Quarterly data to 2020 was extracted from the BSAC National Outcomes Registry and analysed. Results: 57 organizations submitted data on 27 841 patient episodes and 442 280 OPAT treatment days. A diverse range of infections and antimicrobials were reported with a mean OPAT treatment duration of 16.7 days (adults) and 7.7 days (paediatrics). In adults, the top five conditions treated were skin and soft tissue (27.6%), bronchiectasis (11.4%), urinary tract infections (7.6%), and diabetic foot infections (5.5%). Ceftriaxone followed by teicoplanin, ertapenem and piperacillin/tazobactam were the most-used antimicrobials. A median of 1.4 vascular-device-related complications were observed per 1000 OPAT treatment days (range 0.11 to 10.4) with device infections in 0.3 per 1000 OPAT days (range 0.1 to 1.7). Other adverse events (rash, blood dyscrasias, antibiotic-associated diarrhoea) were observed in a median of 1.9 per 1000 OPAT days. OPAT infection outcome (cured/improved) was 92.4% and OPAT outcome (success/partial success) was 90.7%. Conclusions: This report demonstrates the safety, breadth, and complexity of modern UK OPAT practice. Future analyses of OPAT data should focus on infection- and service-specific quality indicators. OPAT registries remain central to planning and assessing safe, effective, and efficient delivery of patient-centred care and should be an important focus for UK and global OPAT practice.